Measurement of acoustic dissipation in an experimental combustor under representative conditions. (3rd March 2017) - Webster, Samuel; Hardi, Justin; Oschwald, Michael
Abstract: The present paper is concerned with experimental estimation of acoustic dissipation under conditions representative of those in a rocket engine combustion chamber. Specifically, the influence of operating and injection conditions on acoustic dissipation is considered. Two experimental and analytical techniques are applied to measure and then compare dissipation rates of the first longitudinal and transverse acoustic modes in an experimental combustion chamber. Comparison between non-combustion and combustion tests showed that combustion chamber damping for the first transverse mode is far greater under combustion conditions. A lesser difference between non-combustion and combustion tests for the first longitudinal mode was found although the damping rates during combustion tests were still higher. A strong relationship between primary injection velocity and dissipation rate was observed, with lower injection velocities leading to decreased damping rates of the first transverse mode. Furthermore, increased film cooling injection rate decreased dissipation rate. The significant influence of representative conditions, specifically injection conditions, on dissipation rate has strong implications for both combustor design and experimental approaches aimed at quantifying dissipation in rocket combustion chambers.